The use of organizational controls and their effects on data manipulation and management myopia: A Japan vs U.S. comparison - Chow, Chee W.; Kato, Yutaka; Merchant, Kenneth A. (Accounting, organizations and society, 1996)
Two prior papers by Merchant (1985b, 1990) have explored the use and effects of five management controls at the profit center level of a large U.S. firm. This study extends the investigation to a crosscultural context. Data were collected from first-line profit center managers at Toshiba — a Japanese manufacturer matched in size and industry to Merchant's (anonymous) U.S. firm. These data were combined with those of Merchant to test four predictions derived from Hofstede's (1980) taxonomy of national culture. The findings supported the predictions that relative to their U.S. counterparts, the Japanese profit center managers were subject to tighter procedural controls and controls via directives given at meetings. Further, when faced with the same level of control tightness, they did not engage in as high a level of dysfunctional activities. However, contrary to prediction, the Japanese managers were subject to significantly tighter controls overall than were the U.S. managers.